A diachronic investigation of the vowels and fricatives in Korean: An acoustic comparison of the Seoul and South Kyungsang dialects. (28th March 2016) - Lee, Hyunjung; Jongman, Allard
Abstract : Although the segmental properties of Kyungsang Korean have been known to be distinct from those of standard Seoul Korean, the increased influence of Seoul Korean on the regional variety casts doubt on the homogeneity of the dialect. The current study investigated whether the acoustic properties of the vowels and fricatives in Kyungsang Korean are retained by both younger and older generations through a comparison with Seoul Korean. Results of acoustic analyses with 38 female Korean speakers differing in dialect (Kyungsang, Seoul) and age (older, younger) showed that the younger Kyungsang speakers did not maintain the vowel and fricative features unique to their regional dialect, but rather approximate those of standard Seoul Korean. In the acoustic study of vowels, measures of formant frequencies showed that the younger Kyungsang and Seoul speakers share seven vowels, which result from the split of /ʌ/–/ɨ/ in Kyungsang and the merger of /e /–/ε/ in Seoul Korean. In the acoustic study of fricatives, measures of fricative duration and center of gravity showed that while the two-way fricative contrast is less distinct for older Kyungsang speakers, younger speakers clearly distinguish the two fricatives similar to Seoul speakers. As a consequence of these generational changes in Kyungsang Korean, the six vowels and lack of a fricative contrast exhibited by older generations have given way to seven vowels and a clear distinction between fortis and non-fortis fricatives for younger generations. Based on the similarities in segmental properties between younger Kyungsang and Seoul speakers, it appears that the diachronic sound change is underway in South Kyungsang Korean under the influence of Seoul Korean.